Ceramic Production and Exchange among the Virgin Anasazi, 30 Years Later. Issue 4 (2nd October 2019) - Allison, James R.
Abstract : At the 1988 SAA annual meeting in Phoenix, Margaret Lyneis presented a paper with the title Ceramic Production and Exchange among the Virgin Anasazi. In that paper, she presented evidence that much of the pottery found on archaeological sites in the Moapa Valley of southeastern Nevada was in fact produced 70–100 km to the east. This pottery was made from distinctive raw materials found near the north rim of the western Grand Canyon. That 1988 SAA paper inspired much subsequent research, including my doctoral dissertation, which examined ceramic distributions across the western part of the Virgin region. In this paper, I update and expand on my earlier study. This analysis adds detail to Lyneis's original arguments, but demonstrates that she was largely correct. From about AD. 1050–1125, small-scale Virgin region settlements were linked by intensive ceramic exchange networks that crossed long distances and rugged terrain.